Постсоветское общество: Новое Средневековье - Мелков, Ю. (Социология: теория, методы, маркетинг, 2008)
The article is devoted to investigation of feudal or quasi-feudal elements present in the structure of contemporary society of post-soviet Ukraine, as well as other countries. It is shown that the new elites quite differ from traditional up per classes in accepting no social responsibility. Due to the privatization (re-feudalization) of social sphere, elites are now value-restricted while sharing market cosmopolitism values of the global ‘new estate’ and rejecting traditional cultural values.